Library usage patterns of the Pangasinan State University, Bayambang Campus as affected by students' personal attributes, library resources, facilities and services - Iglesias, Blesilda Q.; Buenrostro, Juan Jr. C.; Arellano, Clarita A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1994)
This is an analysis of the library usage patterns of the students of Pangasinan State University, Bayambang Campus. The objectives of the study are: 1) To determine the relationship between the personal attributes of the students and their library usage pattern; 2) To determine the status of the resources, facilities and services of the PSU Bayambang Campus Library as assessed by the students.
This study used the normative survey research method with the questionnaire as the tool in gathering data. The subjects of the study were the students of the Pangasinan State University Bayambang Campus enrolled in the second semester, 1992-1993. The respondents were randomly sampled from about twenty percent of the total student population. Although the students were all education students, majority of them are Bachelor in Elementary Education (BEE) and belong to the first and second year levels. They were predominantly females aged 18-19 years of age.
The findings of the study show that the students seldom (44.4 percent) and frequently (43.5 percent) use the library. Majority of the respondents judged the help given by the library staff as fair. Majority of the respondents perceived the library staff as more helpful than effective. Majority of the respondents considered the book collection inadequate. However, the periodicals collection was found to be adequate. The size of the Reading Room was judged as narrow/small by majority of the respondents. The personal attributes of the students such as course, year level, gender, distance of residence from school, academic performance, use of other resources, presence of personal library and attendance to library orientation have partial significant relationship with the dependent variable, i.e., library usage pattern. Thus, the null hypothesis which stated that there was no significant relationship between the personal attributes and their library usage pattern was not fully rejected. With regards to the presumed relationship between the library resources, facilities and services as assessed by the students, and their library usage patterns, the result of the statistical test revealed that there was partial significant relationship. Thus the null hypothesis which stated that there was no significant relationship between the two variables was not fully rejected.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library resources; Library use studies--Phililppines--Pangasinan.; Pangasinan State University. Bayambang Campus--Information services